2023
DOI: 10.1097/md.0000000000032463
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health coaching for job stress management among technical college teachers: Implications for educational administrators

Abstract: Background: The need for stress management strategies has been empirically investigated and supported considering demands in workplaces. However, some people in public offices do not seem to have been exposed to occupational health strategies that could reduce the adverse impacts of stress on job productivity and quality of life. Consequently, they become susceptible to mental health disturbances requiring the attention of occupational therapists. Given this, we studied the impact of occupational health coachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
11
1
1
Order By: Relevance
“…The corresponding result of hypothesis revealed there is significant moderating effect of gender on flood-induced anxiety disorder among farmers. The present study disagrees with Ogakwu et al [ 34 ] who revealed that gender and stress do not significantly influenced academic stress of students in Nigeria. The different finding with regard to gender could be due to the fact that both researches involve different populations (adult parent, who were farmers and university students).…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…The corresponding result of hypothesis revealed there is significant moderating effect of gender on flood-induced anxiety disorder among farmers. The present study disagrees with Ogakwu et al [ 34 ] who revealed that gender and stress do not significantly influenced academic stress of students in Nigeria. The different finding with regard to gender could be due to the fact that both researches involve different populations (adult parent, who were farmers and university students).…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…Also, some past studies did not consider the value of long hours in the intervention process. [20][21][22][23] Consistent and significant outcomes of past studies revealed that REBT would decrease psychological disturbances affecting people. [24][25][26] The likelihood that the REBT treatment will boost self-esteem is far less certain.…”
Section: Research Gaps and Rationale For The Studymentioning
confidence: 94%
“…Also, some past studies did not consider the value of long hours in the intervention process. [20–23]…”
Section: Introductionmentioning
confidence: 99%
“…La salud mental es un área importante que debe abordarse en todos los ambientes laborales, la incorporación de terapias y consejeros ayudó a reducir la susceptibilidad a padecer trastornos mentales y disminuir las tasas de estrés laboral (Ogakwu et al, 2023), en general las intervenciones psicológicas a nivel individual han expuesto resultados prometedores en el bienestar psicológico de los empleados (Kubzansky et al, 2018).…”
Section: Manejo De Hábitos Nocivosunclassified